2010
DOI: 10.1177/1077801210375977
|View full text |Cite
|
Sign up to set email alerts
|

Fact or Fiction? Gender Issues Related to Newspaper Reports of Intimate Partner Homicide

Abstract: The present study compared newspaper articles reporting female-perpetrated intimate partner violence (IPV) homicides with those reporting male-perpetrated IPV homicides. Domestic violence was not mentioned in 72% of the articles. Female-perpetrated IPV homicide, although relatively rare, was not portrayed as more newsworthy nor did it receive more coverage when compared to male-perpetrated IPV homicide. When analyzing explanations for homicides given in newspaper reports, as well as descriptors used to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 16 publications
2
39
2
2
Order By: Relevance
“…Another consistent finding in the literature is that media portrayals of IPV are primarily episodic in nature (Carlyle et al, 2008;McManus & Dorfman, 2003;Wozniak & McCloskey, 2010). In other words, most reporting rendered the instances of IPV as merely isolated criminal events devoid of broader societal context.…”
Section: Media Portrayals Of Intimate Partner Violencementioning
confidence: 66%
See 3 more Smart Citations
“…Another consistent finding in the literature is that media portrayals of IPV are primarily episodic in nature (Carlyle et al, 2008;McManus & Dorfman, 2003;Wozniak & McCloskey, 2010). In other words, most reporting rendered the instances of IPV as merely isolated criminal events devoid of broader societal context.…”
Section: Media Portrayals Of Intimate Partner Violencementioning
confidence: 66%
“…Carlyle and colleagues (2008) conducted a content analysis of 395 nationally representative, IPVrelated U.S. newspaper articles published between 2002 and 2003 and found that newspaper framing of IPV is overwhelmingly episodic in nature (88.3%). Similarly, Wozniak and McCloskey (2010) examined U.S. newspaper articles covering incidents of IPV perpetrated by men (n 5 70) and women (n 5 30) and found that 99% failed to cast IPV in the "broader context," that is, as a widespread social phenomenon (p. 947). Conversely, Ryan, Anastario, and DaCunha (2006) investigated how the implementation of a best practices handbook 3 on reporting domestic violence murders affected the coverage of this topic by conducting a qualitative content analysis of the articles written by 37 reporters over time, both prehandbook (n 5 103, 1996-1999) and posthandbook (n 5 172, 2000-2002).…”
Section: Media Portrayals Of Intimate Partner Violencementioning
confidence: 98%
See 2 more Smart Citations
“…This process yielded 24 themes and concepts (see figure 2a and 2b). These can be grouped into seven broad categories: (a) articles about the judicial disposition or policing of a specific case; (b) articles on individual victims and/or perpetrators that centered on the characteristics of victims and/or perpetrators, a theme found in many previous analyses of newspaper reporting on domestic violence (Wosniak & McCloskey, 2010); (c) reports that outlined policy and legislative developments; (d) reports on practical measures, including service provision, aimed at addressing FM and helping victims; (e) articles seeking to estimate the scale of the problem in the United Kingdom; (f) articles on prevention (a small, but defined subset); and (g) articles on the context, nature, and causes of FM. The last category included articles that discussed FM within the broader context of VAW or wide-ranging debates on community cohesion, multiculturalism, speaking English at home, immigration, Muslims/Islam, and minority communities and their culture and traditions, including arranged and transnational marriage.…”
Section: Representing Fmmentioning
confidence: 99%